Analisis Perubahan Penggunaan Lahan Pertanian Ke Non Pertanian di Kecamatan Kedungkandang Kota Malang - Purwanto, Tri; Jamil, Achmad Maulana Malik; Suprianto, Agung (PT. Pubsains Nur Cendekia, 2023)
The need for land in urban areas is influenced by economic factors that cannot be avoided. This study aims to: 1) analyze land use changes from agriculture to non-agriculture in Kedungkandang District; and 2) knowing several factors that influence it. The research method used is a quantitative method by conducting a survey in Kedungkandang District, Malang City. Quickbird imagery was used to analyze changes in land use from 2006 to 2016. The analysis results obtained by changes in land use in Kedungkandang District, indicating that the largest changes in agricultural land were located in Cemorokandang Village of 67.9 ha or the equivalent of 25.51%, the average change land use of 24.06 ha or the equivalent of 8.3% while the area that experienced the least land change was located in the Kotalama Village of 1.66 ha or the equivalent of 0.57%. While the factors that influence changes in land use in Kedungkandang District are economic factors and public interest.